2021
DOI: 10.1530/eje-20-1073
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of age on survival in radioiodine refractory differentiated thyroid cancer patients

Abstract: OBJECTIVE The objectives of our study were to analyze the influence of age on the survival of patients with RAIR-DTC and to determine their prognostic factors according to age. METHODS This single centre, retrospective study enrolled 155 patients diagnosed with RAIR-DTC. The primary end point was overall survival (OS) according to different cut-off (45,55,65,75 years). Secondary endpoints were progression free survival (PFS) and prognostic factors in patients under and over 65 years. RESULTS Median O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Another observation in our study was the fact that patients who experienced biochemical and radiological cure were significantly younger, consistently with the recent increase of the age cut-off for risk stratification in PTC from 45 to 55 years in the TNM-8 ( 23 ): patients experiencing progression were older than 55 in this study. Recent data also confirm increased overall survival in patients with radioiodine refractory disease younger than 45 ( 24 ). A further result was that patients, who could not be cured by surgery, more frequently displayed loco-regional recurrence instead of lymph nodal recurrence.…”
Section: Discussionmentioning
confidence: 76%
“…Another observation in our study was the fact that patients who experienced biochemical and radiological cure were significantly younger, consistently with the recent increase of the age cut-off for risk stratification in PTC from 45 to 55 years in the TNM-8 ( 23 ): patients experiencing progression were older than 55 in this study. Recent data also confirm increased overall survival in patients with radioiodine refractory disease younger than 45 ( 24 ). A further result was that patients, who could not be cured by surgery, more frequently displayed loco-regional recurrence instead of lymph nodal recurrence.…”
Section: Discussionmentioning
confidence: 76%
“…In RAI refractory patients, an age of >60 years-old (HR = 8.498, CI 95:1.555–46.427, p = 0.0135) and the male gender (HR = 5.435, CI 95:1.261–23.256, p = 0.0231) negatively affected patients’ survival [ 176 ]. However, Saie et al [ 177 ] observed a reduction in the overall survival (4.65 years, 95% CI: 2.04–5.68, p = 0.0008) only in patients older than 75 years, while they failed to prove an association between age and progression-free survival in their cohort. Other reports did not confirm the negative prognostic role of age in PDTCs, even considering different thresholds [ 178 ].…”
Section: Rai Refractorinessmentioning
confidence: 94%
“…In this study, age was a significant independent factor for survival in patients with FTC. Several studies have shown that the prognosis of elderly patients with TC is relatively poor ( 20 - 22 ). In addition, the relationship between older age and poor survival prognosis has been reported in many types of cancer ( 23 - 25 ).…”
Section: Discussionmentioning
confidence: 99%